Prolonged febrile illness due to CTX-M-15 extendedspectrum β-lactamase-producing Klebsiella pneumoniae infection in Nigeria - Oladipo A. Aboderin; Olufemi Adefehinti; Babatunde W. Odetoyin; Amadin A. Olotu; Iruka N. Okeke; Olugbenga Adeodu (AOSIS, 2012)
We report on an 8-year-old patient with septicaemia unresponsive to therapy for five weeks. Undetected, extended-spectrum β-lactamase (ESBL) production by the infecting Klebsiella strain was regarded as responsible for treatment failure. Intravenously administered imipenem during the sixth week led to sustained resolution of fever. Resource-limited hospitals can incur prohibitive costs from ESBL-producer infections because of diagnostic limitations and consequent treatment failure involving prolonged supportive therapy.